(3QSGdI aj Yde GdMQa GdQhMGfjs - (3YHO GdLejd GdehUdj GdbGOQjs ((3eUWai Hf jhfS s)
(3ChdgG (B:s
(3GdMeO ddg GdPj Vd LfS GdCOej Ydi SGFQ ef GdCfhGY hCWdY eG TBA Ydi eG TBA s
(3BNQgG (B:s
(3hJCNP YOO MQhag hJfXQ Cj GdCSeGA GdehGabg Edi Pdc GdGSe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs